Evaluasi Kebijakan Pemekaran Wilayah di Kabupaten Bekasi Berdasarkan Undang-Undang Nomor 32 Tahun 2004 Tentang Pemerintahan Daerah (Studi Kasus Kecamatan Tarumajaya) - Nuraini, Siti (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
One of the strategy conducted by Local Government to increase society's prosperity through the increasing of public service quality is done by area expansion policy, like what is done by Local Government of Bekasi. The result of the area expansion policy research in Bekasi District through Sub District expansion and the implementation of Bekasi Regent regulation Number 6 Year 2005 about Devolution of A part of Authority To Handle A Part of Local Autonomy Business toward The Head of Sub District and Bekasi regulation Number 5 Year 2010 about The Permit Implementation, Non Permit, and the Devolution of A Part of Authority To Handle A Part of Local Autonomy Bussiness in Bekasi District has not been optimal in the implementation. It shows that the Local Government Apparatus Performance in giving the service has not been optimal, it is supported from the questioner proliferation toward the society in Tarumajaya Sub District which result is that the performance of Government apparatus in giving the service is not quite good. Thus, the evaluation toward the area expansion in Bekasi has not been suitable with the purpose of Constitution Number 32 Year 2004 About Local Government which is increasing the public service to embody the prosperity for society.